Insecure guardians: enforcement, encounters and everyday policing in post-colonial Karachi - Waseem, Zoha (Oxford scholarship online Political Science, 2022)
The police force is one of the most distrusted institutions in Pakistan, notorious for its corruption and brutality. In both colonial and post-colonial contexts, directives to confront security threats have empowered law enforcement agents, while the lack of adequate reform has upheld institutional weaknesses. This exploration of policing in Karachi, Pakistan's largest city and financial capital, reveals many colonial continuities.